Razumevanje timskega dela v socialnem varstvu - Mesec, Bojana (Socialno delo, 2015)
In their operations, social welfare organizations depend on teamwork. The article tries to explain concepts that can be met in teamwork or may affect the quality of services provided by organizations in the social care. Here social workers can be key factors and it is important for them to carry out their work professionally. The approach to teamwork, developed by social work, is based on balanced participation of all members, on developing a team, on flexible division of labour and on primacy of tasks over roles. In this process, social workers often act as translators between the context of professional treatment and everyday context of the user. For social work profession, teamwork is a useful tool in areas where social workers are faced with decision-making, management and planning. The article attempts to clarify the issue of cooperation of various disciplines for the purpose of finding a solution to a problem. Here social work it is not independent of other subsystems such as justice, education, health, police, etc. However, none of these subsystems can interfere with development of professional identity of social work. It is therefore necessary that all disciplines contribute to a common dialogue, which must meet professional and scientific criteria for each of the disciplines, but must be theoretically and practically relevant for the achievement of specific objectives of social security.
Keywords: team; timsko delo; group dynamics; socialno varstvo; communication; skupinska dinamika; interdisciplinary cooperation; komunikacija; interdisciplinarno sodelovanje; social work; socialno delo